Великдень – найзначніше християнське свято - Алпатов, В. М. (My University, 2020)
In this article the author to describe the main thing about Ukrainian traditions and customs, such as Easter and the Easter egg. Our people have a rich culture, a huge treasure of which is treasured by many generations. Since ancient times, life wisdom and lifestyle guidelines have come to us.
Keywords: культурне розмаїття; українознавство; традиції; культура